Determination of Dyeing Properties in Petals of Different Safflower (Carthamus tinctorius L.) Varieties - Basalma, Dilek; Kayabasi, Nuran; Gurbuz, Bilal (Asian Journal of Chemistry, 2010)
The aim of the study is to determine weld dyeing properties by using different mordants and dyeing methods. A premordanting method was used in the dyeing of woolen yarn with petals of safflower varieties. In this study, Dincer, Yenice and Remzibey safflower varieties (thornless, thornless, thorny) and control, N5, N10, N15, kg/da nitrogen doses were used. The experiment was carried out in randomized complete block design with 3 replications that were grown in the Department of Field Crops, Faculty of Agriculture, Ankara University. Petals of safflower that were obtained were exposed to dyeing without using mordant and by using copper sulphate, iron sulphate, potassium bichromate, sodium chloride, sodium sulphate mordants. Colours obtained as a result of the dyeing were evaluated subjectively and colourful wools were assessed in terms of light, rubbing and water drop fastness values.